The p53 breast cancer tissue biomarker in Indian women - Patil V (Dove Medical Press, 2011)
Vinayak W Patil1, Mukund B Tayade2, Sangeeta A Pingale1, Shubhangi M Dalvi1, Rajesh B Rajekar1, Hemkant M Deshmukh1, Shital D Patil1, Rajeev Singhai11Department of Biochemistry, 2Department of General Surgery, Grant Medical College and Sir JJ Group of Hospitals, Mumbai, IndiaBackground: Combination chemotherapy is highly effective in locally advanced breast cancer. A negative expression of biomarker p53 indicates a higher chance of responding to this regimen. Patients' p53 status may be used as a biological cancer marker to identify those who would benefit from more aggressive treatments.Aims: The role of p53 in modulating apoptosis has suggested that it may affect the efficacy of anticancer agents. p53 alterations in 80 patients with locally advanced breast cancer IIIB undergoing neoadjuvant chemotherapy were prospectively evaluated.Materials and methods: Patients received three cycles of paclitaxel (175 mg/m2) and doxorubicin (60 mg/m2) every 21 days. Tumor sections were analyzed before treatment for altered patterns of p53 expression, using immunohistochemistry and DNA sequencing.Results: An overall response rate of 83.5% was obtained, including 15.1% complete pathological responses. The regimen was well tolerated with 17.7% grade 2/3 nausea and 12.8% grade 3/4 leukopenia. There was a statistically significant correlation between response and expression of p53. Of 25 patients who obtained a complete clinical response, only two were classified as p53-positive (P = 0.004, χ2). Of 11 patients who obtained a complete pathological remission, one was positive (P = 0.099, χ2).Conclusion: Immunohistochemical (IHC) analysis has been shown to be a prognostic factor for patients with breast cancer in India. Paclitaxel is one of the most promising anticancer agents for the therapy of breast cancer, where it has also shown activity in tumors resistant to doxorubicin.Keywords: breast cancer, doxorubicin, p53, paclitaxel, cancer tissue biomarkers, neoadjuvant chemotherapy, immunohistochemistry, infiltrating duct cancer